Speckle-Tracking Echocardiographic Layer-Specific Strain Analysis on Subclinical Left Ventricular Dysfunction in Patients With Primary Aldosteronism. (21st November 2018) - Wang, Dian; Xu, Jian-Zhong; Chen, Xin; Chen, Yi; Shao, Shuai; Zhang, Wei; Zhu, Li-Min; Xu, Ting-Yan; Li, Yan; Wang, Ji-Guang
Abstract: BACKGROUND: Primary aldosteronism (PA) may cause myocardial injury. We investigated myocardial dysfunction using speckle-tracking echocardiographic (STE) layer-specific strain in patients with PA. METHODS: Our study included 62 patients with PA (33 aldosterone-producing adenoma [APA] and 29 idiopathic hyperaldosteronism [IHA]) and 30 patients with primary hypertension. STE was acquired using the GE Vivid E9 equipment. The longitudinal (LS) and circumferential (CS) layer-specific strains of the endocardium, midmyocardium, and epicardium (LSendo, LSmid, LSepi, CSendo, CSmid, and CSepi) were obtained using the EchoPAC BT13 workstation. RESULTS: Patients with APA, compared with those with primary hypertension and IHA, had a significantly ( P < 0.001) lower serum potassium concentration and plasma renin activity, and higher 24-h urinary aldosterone, plasma aldosterone concentration, and aldosterone-to-renin ratio. Left ventricular ejection fraction was normal in all patients (58–60%). Layer-specific strain showed decreasing gradient from the endocardium to epicardium in all 3 groups ( P < 0.01). However, LSendo and CSendo were lowest in APA (−20.2 ± 2.3% and −33.3 ± 3.2%), intermediate in IHA (–22.1 ± 1.9% and −35.7 ± 2.8%) and highest in primary hypertension (–24.1 ± 2.1% and −38.9 ± 3.1%, P < 0.001). Similar trends were observed for LSmid, LSepi, CSmid, and CSepi, but statistical significance was only reached for the comparison between APA and primary hypertension ( P < 0.001), but not others ( P > 0.05). Layer-specific strain was significantly correlated with plasma aldosterone concentration for all echocardiographic parameters ( r = −0.69 to −0.53, P < 0.001) in all 3 groups. CONCLUSIONS: Patients with PA, especially APA, had impaired regional systolic function with myocardial deformation changes at similar levels of blood pressure, probably because of elevated plasma aldosterone concentration.